Atrial fibrillation in patients with chronic lymphocytic leukemia (CLL). Issue 7 (3rd July 2017) - Shanafelt, Tait D.; Parikh, Sameer A.; Noseworthy, Peter A.; Goede, Valentin; Chaffee, Kari G.; Bahlo, Jasmin; Call, Timothy G.; Schwager, Susan M.; Ding, Wei; Eichhorst, Barbara; Fischer, Kirsten; Leis, Jose F.; et al.
Abstract: Although preliminary data suggests that ibrutinib may increase risk of atrial fibrillation (AF), the incidence of AF in a general cohort of chronic lymphocytic leukemia (CLL) patients is unknown. We evaluated the prevalence of AF at CLL diagnosis and incidence of AF during follow-up in 2444 patients with newly diagnosed CLL. A prior history of AF was present at CLL diagnosis in 148 (6.1%). Among the 2292 patients without history of AF, 139 (6.1%) developed incident AF during follow-up (incidence approximately 1%/year). Older age ( p  < .0001), male sex ( p  = .01), valvular heart disease ( p  = .001), and hypertension ( p  = .04) were associated with risk of incident AF on multivariate analysis. A predictive model for developing incident AF constructed from these factors stratified patients into 4 groups with 10-year rates of incident AF ranging from 4% to 33% ( p  < .0001). This information provides context for interpreting rates of AF in CLL patients treated with novel therapies.